МОДЕЛЬ ОПТИМАЛЬНОГО РОЗПОДІЛУ ГІДРОРЕСУРСІВ ГЕС З РЕЗЕРВУВАННЯМ ПОТУЖНОСТЕЙ ДЛЯ НАДАННЯ ДОПОМІЖНИХ ПОСЛУГ АВТОМАТИЧНОГО ВІДНОВЛЕННЯ ЧАСТОТИ - Парус, Є.В.; Блінов , І.В.; Мірошник, В.О.; Рибіна, О.Б.; Олефір, Д.О.; Сичова, В.В. (Інститут електродинаміки НАН України, Київ, 2024)
The publication is devoted to the development of a mathematical model for the optimal allocation of hydro resources among hydroelectric units of HPPs for the production of electric energy and the provision of automatic frequency restoration reserves with an asymmetric adjustment range. The concept of building a mathematical model for the optimization problem is presented. The main goal of the optimization is to maximize the benefit of the power generation company from the use of available hydro resources for the production of electricity and the provision of services for the regulation of IPS of Ukraine modes. Areas of determining the main characteristics of the operation mode of hydropower units of HPPs were studied and a system of restrictions on the load capacity of hydrounits was formed. A system of restrictions to control the balance of water resources in the reservoir and a system of restrictions to control the values of water runoff for hydroelectric power stations have been defined. For the level of the power generating company, a system of restrictions on the control of the minimum values of the volumes of electricity and ancillary services for the fulfillment of already concluded agreements, as well as a system of restrictions on the control of the volumes of electricity and ancillary services within the predicted volumes of market demand, has been formed. The structure is substantiated and the components of the target function are described. Approaches to solving the problem of forecasting the amount of electrical energy imbalances on the balancing market of Ukraine are defined. Peculiarities of the process of finding optimal solutions regarding the loading levels of hydropower units with available hydro resources have been studied. The presence of the effects of "economic impracticality of the full use of available water resources" was noted, and the main consequences of the manifestations of this effect were investigated. References 12, figures 3, tables 2.